A comparison of the efficacy and safety of traditional Chinese medicine external treatment for the hyperemesis gravidarum: A protocol for systematic review and network meta-analysis. Issue 45 (6th November 2020) - Yan, Rugen; Zhan, Junyi; Liu, Gongxue; Li, Changzhong; Cai, Pingping; Chen, Yin; Cao, Huanze
Abstract: Background: The symptoms of frequent nausea and vomiting, inability to eat, and fluid imbalance caused by hyperemesis gravidarum (HG) seriously impact the quality of life of pregnant women. In some serious cases, it is even necessary to terminate the pregnancy, and threatens the life of the pregnant woman. A great many of studies have proved that HG can be effectively treated by traditional Chinese medicine (TCM) external treatment. Nevertheless, its relative effectiveness and safety haven't yet been confirmed because of the variety of TCM external treatment. Therefore, we will use the method of network meta-analysis to verify the effectiveness and safety of different types of TCM external treatment for the HG. Methods: In this study, English and Chinese literatures that meet the requirements will be searched in EMBASE, PubMed, Cochrane Library, Web of Science, CnKI, VIP, Wanfang, and CBM. Regardless of whether blinding is used or not, all randomized controlled trials (RCTs) using TCM external treatment for the HG will be included. Then, Stata 16.0 will be used to conduct a series of pairwise meta-analysis. WinBUGS 1.4.3 and Stata 16.0 will be used to conduct Bayesian network meta-analysis to evaluate the relative results of different TCM external treatments for the HG. The quality included in the study will be evaluated through the classification of Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: This study will evaluate the effectiveness and safety of TCM external treatment for the HG according to the primary and secondary outcomes, and we rank different kinds of TCM external treatments in accordance with effectiveness. The primary outcomes are the intensity of nausea and vomiting. Secondary outcomes include quality of life, adverse outcome of pregnant women, adverse outcome of fetal, duration of hospitalization and so on. Conclusion: This study will provide more convincing and detailed information of TCM external treatment for the HG, and the reference value for clinical treatment. INPLASY registration number: INPLASY 202090089.